2011
DOI: 10.1111/j.1742-481x.2011.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical grape (Vitis vinifera) seed extract promotes repair of full thickness wound in rabbit

Abstract: In recent years, oxidative stress and free radicals have been implicated in impaired wound healing. Grape (Vitis vinifera) seed extract (GSE) possesses anti-inflammatory and antioxidant properties. The present study was undertaken to assess the potential activity of grape seed hydroalcoholic extract in wound healing in rabbits. Rabbits of either sex were subjected to a 20 × 20 mm square excision made over the skin of the back. The animals were randomly divided into seven experimental groups, as negative and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…Grape (Vitis vinifera) seed extract exhibits anti-inflammatory and antioxidant features [19]. It has been explained that topical application of grape seed proanthocyanidin extract promotes wound restoration.…”
Section: Resultsmentioning
confidence: 99%
“…Grape (Vitis vinifera) seed extract exhibits anti-inflammatory and antioxidant features [19]. It has been explained that topical application of grape seed proanthocyanidin extract promotes wound restoration.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, topical grape seed extract 2% w/w in a eucerin base had significant wound healing effects in rabbits and this effect was greater than that of topical phenytoin (Hemmati et al ., ).…”
Section: Pharmacological Effectsmentioning
confidence: 97%
“…In line with our findings, their findings confirmed the positive effects of grape seed extract on wound healing. In another study, Hemmati et al (2011) also found that 2% grape seed extract accelerated the process of wound contraction and closure and reduced wound healing time from 20 to 13 days (20). Nayak et al (2010) also assessed the effects of grape skin powder on full-thickness skin lesions in mice and found that complete wound contraction and healing occurred thirteen days after the beginning of their treatment (21).…”
Section: Discussionmentioning
confidence: 97%